O contexto e perfis característicos da mortalidade materna em Belo Horizonte (MG), 2003-2010 - Lilian Valim Resende (2013)
This study aims to assess maternal mortality in Belo Horizonte city, in the period from 2003 to 2010, in order to identify profiles associated with its occurrence and associated factors. Furthermore, we intended to understand the families perception regarding maternal deaths and the circumstances that led to the end of these deaths, both from the point of view of the actions that could have prevented the deaths, as those related to health, socioeconomic and behavioral factors that might have contributed to the outcome. The work was divided into two stages. In the first one, the database was organized based on the collection of information on maternal deaths of Maternal, Fetal and Infant Death Prevention Committee, in the Municipal Health Department of Belo Horizonte (BH-SMSA). The second stage consisted of in-depth analysis of interviews conducted with families of women who died. In Belo Horizonte, in the researched period, there were 180 maternal deaths, 87 (48.3%) direct obstetric, 31 (17.2%) indirect obstetric, 19 (10.6%) late maternal, 33 (18.3%) non-obstetric and 10 (5.6%) considered unconcluded, hence unrated by the Committee. Two groups of maternal deaths were identified through the Two-Step Cluster method. The first group of deaths that occurred in post-cesarean birth, women who underwent prenatal and gave birth to a live baby and died primarily by hypertensive disorders and puerperal infections. The second group consisted of deaths of unmarried women, users of the public health system, who died from complications during pregnancy or induced abortion. The reports from relatives suggest that there are flaws in the health care provided to the woman in Belo Horizonte regardless the health system is public or private. Deficiencies in the training of health professionals were also presented, including issues from right qualification through humanistic aspects in the provision of care. Maternal deaths recorded in the city of Belo Horizonte between 2003 and 2010 were strongly associated with issues related to reproductive rights prior to pregnancy, abortion and pregnancy care, childbirth and the postpartum period, with clear evidence of preventability.